2009
DOI: 10.1038/tpj.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predictors of response to antidepressants in the GENDEP project

Abstract: The objective of the Genome-based Therapeutic Drugs for Depression study is to investigate the function of variations in genes encoding key proteins in serotonin, norepinephrine, neurotrophic and glucocorticoid signaling in determining the response to serotonin-reuptake-inhibiting and norepinephrine-reuptake-inhibiting antidepressants. A total of 116 single nucleotide polymorphisms in 10 candidate genes were genotyped in 760 adult patients with moderate-to-severe depression, treated with escitalopram (a seroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 38 publications
3
148
2
2
Order By: Relevance
“…This analysis confirmed that associated genetic markers were independent predictors of increase in suicidal ideation during treatment. Moreover, supporting this result, neither BDNF, NTRK2, nor ADRA2A genes were found to be predictors of overall response to antidepressants in the same sample (Uher et al, 2009a).…”
Section: Limitationsmentioning
confidence: 61%
“…This analysis confirmed that associated genetic markers were independent predictors of increase in suicidal ideation during treatment. Moreover, supporting this result, neither BDNF, NTRK2, nor ADRA2A genes were found to be predictors of overall response to antidepressants in the same sample (Uher et al, 2009a).…”
Section: Limitationsmentioning
confidence: 61%
“…Subjects in the GENDEP study were recruited from nine European centers if they experienced at least one depressive episode of at least moderate severity (Uher et al, 2009). …”
Section: Discovery Cohort: Colaus|psycolausmentioning
confidence: 99%
“…Uher et al, 2009) were specific to predict treatment response. The substances used for treatment in our study were dual acting substances that modulate both serotonergic and noradrenergic systems in a different way.…”
Section: Volumementioning
confidence: 99%